Renal Cell Carcinoma in the Background of Autosomal Dominant Polycystic Kidney Disease: Report of Two Cases and Review of Literature - Poorva Vias; Shikha Goyal; Renu Madan; Nandita Kakkar; Ridhi Sood; Kannan Periasamy; Rajender Kumar (Indian Journal of Medical and Paediatric Oncology)
Patients with autosomal dominant polycystic kidney disease (ADPKD), especially those with renal failure, carry a higher risk of developing renal cell carcinoma (RCC) compared to the general population. Genetic mutations associated with ADPKD are known but a direct link associated with RCC is still controversial. We discuss the clinical course of two such patients. The first patient was diagnosed with ADPKD at the age of 10 years with an unreported tubulocystic RCC focus on his renal biopsy that was picked up on review 16 years later when he presented with vertebral metastases determined to have originated from the RCC. He was doing well on multikinase inhibitors till 4 years of diagnosis with metastatic disease when he succumbed to progressive disease after 3 lines of systemic therapy. The second patient was diagnosed with ADPKD in middle age and papillary RCC 3 years later. Within 3 months of cancer diagnosis, there was progression to metastatic disease and rapid decline despite systemic therapies. We surmise that the diagnosis of RCC may be missed in ADPKD till the advanced stages. Patients with ADPKD should be monitored regularly with imaging and biopsy if needed. Histology may be varied but once diagnosed, systemic therapies may help disease control.